Evaluation of CGIAR Science Groups: Synthesis Report - Palmieri, Natascia; Haussmann, B.I.G.; Zake, J.; Armstrong, Matthew; Cekova, Diana; Negroustoueva, Svetlana (CGIAR Independent Advisory and Evaluation Service, 2024)
The synthesis objective is to provide evaluative evidence across the three Science Group (SG) evaluations with key findings, conclusions and learnings guided by recommendations. The CGIAR 2030 Research and Innovation Strategy sets priorities for development solutions through 33 initiatives across three interlinked action areas: Systems Transformation, Resilient Agrifood Systems, and Genetic Innovation. CGIAR scientists working on these initiatives are organized into corresponding SGs. Aligned to the external SG Evaluations Terms of Reference and the 2022‒24 Multi-Year Workplan of CGIAR’s Independent Advisory and Evaluation Service (IAES), one evaluation per SG was conducted. Evaluations were commissioned by the CGIAR System Council and executed by IAES with external evaluation support. In line with the CGIAR Evaluation Framework, Policy and Strategy, evaluations combined formative and summative aspects to support learning, steering, accountability, and evidence-based revision of the Portfolio. Evaluations covered SG portfolios from January 2022 to February 2024. This synthesis is based on analysis of the three evaluation reports and includes elements from case studies and deep dives, and results of the online survey and internal audit survey.1 Key users are the System Council, SG management, senior leadership team, centers for learning and steering, and external partners, e.g., funders, policymakers, and national governments and organizations.